1980
DOI: 10.3109/01443618009067360
|View full text |Cite
|
Sign up to set email alerts
|

Routine ultrasound before termination of pregnancy

Abstract: Publication details, including instructions for authors and subscription information: http://www.tandfonline.com/loi/ijog20 Journal of Obstetrics and Gynaecology of the British Commonwealth 76,603-609. Robinson H. P. (1973) Sonar measurement of fetal crown-rump length as a means of assessing maturity in the first trimester of pregnancy. British Medical Jortrnal4,28-3 1. Sanders R. C., Curtin M. and Tapper A. (1975) Ultrasound in the management of elective abortion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1985
1985
2008
2008

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…I am glad to have agreed with the findings of our colleagues for the last 20 years. Law and Wilkins 3 had even earlier reported similar results and suggested that scanning contributed much to management for these women. Our study and this new one do so as well.…”
mentioning
confidence: 58%
“…I am glad to have agreed with the findings of our colleagues for the last 20 years. Law and Wilkins 3 had even earlier reported similar results and suggested that scanning contributed much to management for these women. Our study and this new one do so as well.…”
mentioning
confidence: 58%